Citizenship construction and social capital for the local development of the Lara state communities of Venezuela. university extension experience systematization (Revista Venezolana de Salud Pública, 2018)
This paper has as a goal to present the reconstruction of an experience in the setting of a University Extension project, its critical analysis as well as the knowledge and lessons learned through the systematization of facts and activities carried out in itself over four years, in its two major themes a) Management and Promotion from the Direction of University Extension, projects that improve life condition of the population, strengthening the social capital and citizen construction in the Lara state communities and b) Implementation within specific extension projects of the conditions for the practice of the social capital own elements, such as: nets formation, capacities production, spread of the application of values like trust, solidarity, cooperation, besides promoting civic conscience in its participants. Results are presented as the orderly reconstruction of the experience and lessons learned in theorical-conceptual, methodological aspects.
Keywords: Social phenomena; social capital; citizenship; University Extension